Adaptive image brightener in binarization problems of the text documents - Загребнюк, Віктор Іванович; Ленік, Дмитро Дмитрович (Eastern-European Journal of Enterprise Technologies, 2012)
Methods and algorithms of preliminary estimate of image quality and global adaptive increase of luminance are present in this paper. It is shown that image with the promoted luminance could be binarized with the use of simple global thresholding binarization methods